Analysis of High School Students' Mathematical Problem-Solving Ability Based on Mathematics Anxiety and Gender - Cinthia Venita Putri; Asih Miatun (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The purpose of this study was to analyze the mathematical problem-solving abilities (KPMM) of high school students based on math anxiety and gender. The methodology use in this study is qualitative, specifically using a case study approach. The study utilized students from SMA Negeri 31 Tangerang Regency, who were in the 11th grade and studying arithmetic sequences and series. The research subjects were six people, two from each category of math anxiety, chosen through purposive sampling using Winstep and based on an analysis of the person map table. The instruments used were a six-item math problem-solving ability test and a 27-item math anxiety questionnaire that had been validated by expert lecturers and mathematics teachers and was therefore feasible to use. Reduction, categorization, synthesis, and a conclusion were all used to analyze the data in this study. Based to the study's results, gender did not have a significant impact on students' mathematical problem-solving abilities. However, what distinguished them was the category of math anxiety. Male and female students with high levels of anxiety in maths were only able to fulfil one KPMM indicators, but those with moderate and low levels of anxiety were able to fulfil three.